Study on Application of Quantum BP Neural Network to Curve Fitting - Zhixia Zhang; Yanchang Liu; Jianping Xie (Institute of Advanced Engineering and Science, 2013)
Based on the Quantum mechanics in a Quantum phase-shifted door and two negates controlled both general door, using them as the basic unit composed of activation function neural Network, this paper puts forward a Quantum state with input and output of the Quantum neuron Quantum state model and three layers of Quantum BP neural Network model of Network learning algorithm and performance to carry on the thorough study. Experimental results show that compared with BP neural Network, QBP appears quickly learn and convergent effect, with better fitting ability than the BP neural Network. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3388